Plant growth, biomass production and nutrient accumulation by slash/mulch agroforestry systems in tropical hillsides of Colombia - Barrios, E.; Cobo Borrero, Juan G. (Springer, 2004)
Planted fallow systems under slash and mulch management were compared with natural fallow systems at two farms (BM1 and BM2) in the Colombian Andes. The BM1 site was relatively more fertile than the BM2 site. Planted fallow systems evaluated included Calliandra calothyrsus CIAT 20400 (CAL), Indigofera constricta (IND) or Tithonia diversifola (TTH). During each pruning event slashed biomass was weighed, surface-applied to the soil on the same plot and sub-samples taken for chemical analyses. While Indigofera trees consistently showed significantly greater (p < 0.05) plant height and collar diameter than Calliandra trees at both study sites, only collar diameter in Indigofera was significantly affected at all sampling times by differences between BM1 and BM2. After 27 months, TTH presented the greatest cumulative dry weight biomass (37 t ha 1) and nutrient accumulation in biomass (417.5 kg N ha 1, 85.3 kg P ha 1, 928 kg K ha 1, 299 kg Ca ha 1 and 127.6 kg Mg ha 1) among planted fallow systems studied at BM1. Leaf biomass was significantly greater (P < 0.05) for CAL than IND irrespective of site. However, CAL and IND biomass from other plant parts studied and nutrient accumulation were generally similar at BM1 and BM2. At both sites, NAT consistently presented the lowest biomass production and nutrient accumulation among fallow systems. Planted fallows using Calliandra and Indigofera trees had the additional benefit of producing considerable quantities of firewood for household use.